2002
DOI: 10.1021/ol027125o
|View full text |Cite
|
Sign up to set email alerts
|

Studies Directed toward Asymmetric Synthesis of Cardioactive Steroids via Anionic Polycyclization

Abstract: [reaction: see text] The use of anionic polycyclization (AP) in constructing the steroidal backbone of cardenolides was investigated. The reaction of 2-carbomethoxy-2-cyclohexenone I with the enolate of Nazarov reagent II gave, after decarboxylation and aldol condensation, steroid III with control of stereochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The initial steps of the synthesis, drawn from our previous studies on steroid skeleton synthesis,9–11 were successful (Scheme ). Thus, the union of Nazarov substrate 3 10b with freshly prepared cyclohexenone 2 11, 12 in the presence of Cs 2 CO 3 at 0 °C followed by decarboxylation afforded tricycle 4 with an overall yield of 78 %. Reduction of the resulting aldehyde with Li(Et 3 CO) 3 AlH13 and then protection of the alcohol as its PMB ether14 afforded aldol precursor 5 in 74 % yield over two steps The aldol reaction to form the desired tetracycle 6 in 83% yield occurred in the presence of KHMDS.…”
Section: Methodsmentioning
confidence: 98%
“…The initial steps of the synthesis, drawn from our previous studies on steroid skeleton synthesis,9–11 were successful (Scheme ). Thus, the union of Nazarov substrate 3 10b with freshly prepared cyclohexenone 2 11, 12 in the presence of Cs 2 CO 3 at 0 °C followed by decarboxylation afforded tricycle 4 with an overall yield of 78 %. Reduction of the resulting aldehyde with Li(Et 3 CO) 3 AlH13 and then protection of the alcohol as its PMB ether14 afforded aldol precursor 5 in 74 % yield over two steps The aldol reaction to form the desired tetracycle 6 in 83% yield occurred in the presence of KHMDS.…”
Section: Methodsmentioning
confidence: 98%
“…With these results, we felt necessary to unambiguously assign the absolute configuration of our synthetic (+)- 4 by an independent synthesis route that could use chiral material of well-established absolute configuration. Based on the work of Yamashita, 20 and Deslongchamps, 21 readily available Hajos-Parrish ketone (+)- 6 12 was converted into known aldehyde (+)- 10 in 5 steps and 36% overall yield (Scheme 3). Nucleophilic addition of CH 3 Li in THF delivered the corresponding secondary alcohol as mixture of diastereomers, which converged into methyl ketone (+)- 11 upon oxidation with the Dess-Martin reagent.…”
Section: Resultsmentioning
confidence: 99%
“…Aldehyde (+)- 10 Was prepared in five steps and 36% overall yield from known Hajos-Parrish ketone (+)- 6 12 using the sequence described by Deslongchamps 21 with the following modification: NaBH 4 reduction of the Hajos-Parrish ketone (+)- 6 was carried out using the method of Yamashita and Hirama. 20 Characterization data for (+)- 10 matched those described by Deslongchamps.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the long history of research in this area, the interest in cardenolides continues. Recently reported work on cardenolides includes the total synthesis of digitoxigenin1,5 and ouabain,6 biosynthesis7 and the search for new, less toxic digitalis‐like compounds with better pharmacological properties for therapeutic use 8. It has recently been reported that cardenolides have a growth inhibitory effect on cancer cell lines9 and show antiproliferative10 and cytotoxic11 activity.…”
Section: Introductionmentioning
confidence: 99%